Absence of pontine perforators in vertebrobasilar dolichoectasia on ultra-high resolution cone-beam computed tomography. (21st October 2020) - Dobrocky, Tomas; Piechowiak, Eike I; Goldberg, Johannes; Barvulsky Aleman, Enrique; Nicholson, Patrick; Lynch, Jeremy; Bervini, David; Kaesmacher, Johannes; Agid, Ronit; Krings, Timo; Raabe, Andreas; Gralla, Jan; et al.
Abstract : Background: Vertebrobasilar dolichoectasia (VBDE) is a rare type of non-saccular intracranial aneurysm, with poor natural history and limited effective treatment options. Visualizing neurovascular microanatomy in patients with VBDE has not been previously reported, but may yield insight into the pathology, and provide important information for treatment planning. Objective: To carry out a retrospective analysis of ultra-high resolution cone-beam computed tomography (UHR-CBCT) in patients with fusiform basilar aneurysms, visualizing neurovascular microanatomy of the posterior circulation with a special focus on the pontine perforators. Methods: UHR-CBCT was performed in seven patients (mean age 59 years; two female) with a VBDE, and in 14 control patients with unrelated conditions. Results: The mean maximum diameter of the fusiform vessel segment was 28 mm (range 19–36 mm), and the mean length of the segment was 39 mm (range 15–50 mm). In all patients with VBDE, UHR-CBCT demonstrated an absence of perforating arteries in the fusiform arterial segment and a mean of 3.7 perforators arising from the unaffected vessel segment. The network of interconnected superficial circumferential pontine arteries (brainstem vasocorona) were draping around the aneurysm sac. In controls, a mean of 3.6, 2.5, and 1.2 perforators were demonstrated arising from the distal, mid-, and proximal basilar artery, respectively. Conclusions: The absence of pontine perforators in the fusiform vessel segment of VBDE is counterbalanced by recruitment of collateral flow from pontine perforators arising from the unaffected segment of the basilar artery, as well as collaterals arising from the anterior inferior cerebellar artery/posterior inferior cerebellar artery and superior cerebellar artery. These alternative routes supply the superficial brainstem arteries (brainstem vasocorona) and sustain brainstem viability. Our findings might have implications for further treatment planning.